New trends in migratory and refugee law in Brazil: the expanded refugee definition - Catherine Jane Tinker (Universidade de Santa Cruz do Sul, 2016)
This paper aims to explore new trends in Brazilian refugee and migratory law in the last 20 years. In doing so it addresses the evolution of the definition of “refugee” in Brazil, expanding the eligibility grounds provided by the 1951 Geneva Convention on the Status of Refugees (1951 Convention). Reviewing international and regional refugee law, the article analyzes the broader understanding of the notion of "refuge" and its complexity expressed in regional and national legal frameworks, taking account of lawyers, scholars and activists who criticize the narrow scope of the classical refugee definition from 1951 which has become distant from current refugee voices and struggles. At the domestic level, although the 1980 Aliens Statute (Act. n. 6815/80) is still in effect, there have been important changes in refugee law in Brazil since the implementation of the 1997 Refugee Statute (Act n. 9.474/97), influenced by the 1984 Cartagena Declaration (a regional soft law instrument) regarding the definition of “refugee”, Exploring the interconnection of the Refugee Statute and complementary forms of human rights protection which fall outside the scope of international refugee law, the article concludes that in the specific case of Haitians in Brazil, the broader protections of Brazilian refugee law should be available rather than the complementary system of humanitarian visas.